Evaluation of Heat-sensitive Micronutrients in Fresh, Sun-dried and Solar-dried Capsicum Varieties Grown in Peru - Nagle, Marcus; Jankowsky, Birgit; Peña Pineda, Karla Mónica; Ríos Lobo, Llermé; Jäger, Matthias; Nohr, Donatus; Müller, Joachim (University of Hohenheim, 2021)
1 página